METHODOLOGY FOR TEACHING SECOND-LEVEL PIECES IN ELEMENTARY GRADES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article provides feedback on the methodology and methods of teaching second-level sections in beginner classes, and works with conclusions and recommendations accordingly